Dampak Research-Based Learning Berbasis ChatGPT Terhadap Kemampuan Berpikir Kreatif dalam Menyelesaikan Masalah Mahasiswa - Hasan Basri; Rohmah Indahwati; Dimas Danar Septiadi (Bima Journal of Elementary Education, 2025)
This study aims to examine the impact of ChatGPT-based Research-Based Learning on students' creative thinking skills in problem solving. A mixed-methods approach was used with an experimental design involving two groups: an experimental group that used ChatGPT in research-based learning, and a control group that followed traditional learning. Data were collected through creative thinking tests given before and after the intervention, and analyzed using an Independent Samples T-Test. The results showed that the experimental group experienced a significant improvement in creative thinking skills with a higher average posttest score compared to the control group. The t-test showed a p-value of <0.001, which indicates a very significant difference between the two groups. This study confirms that ChatGPT-based Research-Based Learning is effective in stimulating students' creativity in problem solving, as well as making a positive contribution to the development of critical and innovative thinking skills. Thus, the use of ChatGPT in higher education can be a relevant and effective learning model for improving students' creative thinking skills.